Your Performance Is My Concern: A Perspective-Taking Competition Task Affects ERPs to Opponent’s Outcomes - Yu, Hao; Nan, Weizhi; Yang, Guochun; Li, Qi; Wu, Haiyan; Liu, Xun (Frontiers in Neuroscience, 2019)
Previous research has shown that people have more empathic responses to in-group members and more schadenfreude to out-group members. As a dimension of cognitive empathy, perspective-taking has been considered to be related to the enhancement of empathy. We tried to combine these effects through manipulation of a competitive task with opponents and an in-group partner and investigated the potential effect of in-group bias or the perspective-taking effect on outcome evaluation. We hypothesized that the neural activities would provide evidence of in-group bias. We tested it with a simple gambling observation task and recorded subjects’ electroencephalographic (EEG) signals. Our results showed that the opponent’s loss evoked larger feedback-related negativity (FRN) and smaller P300 activity than the partner’s loss condition, and there was a win vs. loss differential effect in P300 for the opponent only. The principle component analysis (PCA) replicated the loss vs. win P300 effect to opponent’s performance. Moreover, the correlation between the inclusion of the other in the self (IOS) scores and FRN suggests perspective-taking may induce greater monitoring to opponent’s performance, which increases the win vs. loss differentiation brain response to the out-group agent. Our results thus provide evidence for the enhanced attention toward out-group individuals after competition manipulation, as well as the motivation significance account of FRN.